1) 56am + 27mu - 24au - 63m2
2) 56am + 27mu - 24au - ( 63 × 2 )m
3) 56am + 27mu - 24au - 126m
ответ: 126m
Объяснение:
Надеюсь
56am + 24mu - 24au - 56m² = (56am - 56m²) + (24mu - 24au) =
= 56m(a - m) + 24u(m - a) = 56m(a - m) - 24u(a - m) = (a - m)(56m -24u) =
= 8(a - m)(7m -3u)
1) 56am + 27mu - 24au - 63m2
2) 56am + 27mu - 24au - ( 63 × 2 )m
3) 56am + 27mu - 24au - 126m
ответ: 126m
Объяснение:
Надеюсь
56am + 24mu - 24au - 56m² = (56am - 56m²) + (24mu - 24au) =
= 56m(a - m) + 24u(m - a) = 56m(a - m) - 24u(a - m) = (a - m)(56m -24u) =
= 8(a - m)(7m -3u)